Sequencing of the Canine Cytochrome P450 CYP2C41 Gene and Genotyping of Its Polymorphic Occurrence in 36 Dog Breeds - Karakus, Emre; Prinzinger, Clarissa; Leiting, Silke; Geyer, Joachim (Frontiers in Veterinary Science, 2021)
Cytochrome P450 (CYP) drug metabolizing enzymes play an important role in efficient drug metabolism and elimination. Many CYPs are polymorphic and, thereby, drug metabolism can vary between individuals. In the case of canine CYP2C41, gene polymorphism was identified. However, as the first available canine genome sequences all were CYP2C41 negative, this polymorphism could not be clarified at the genomic level. The present study provides an exact characterization of the CYP2C41 gene deletion polymorphism at the genomic level and presents a PCR-based genotyping method that was used for CYP2C41 genotyping of 1,089 individual subjects from 36 different dog breeds. None of the Bearded Collie, Bernese Mountain, Boxer, Briard, French Bulldog or Irish Wolfhound subjects had the CYP2C41 gene in their genomes. In contrast, in the Chinese Char-Pei, Siberian Husky, Schapendoes and Kangal breeds, the CYP2C41 allele frequency was very high, with values of 67, 57, 43, and 34%, respectively. Interestingly, the site of gene deletion was identical for all CYP2C41 negative dogs, and all CYP2C41 positive dogs showed highly homologous sequence domains upstream and downstream from the CYP2C41 gene. CYP2C41 genotyping can now be routinely used in future pharmacokinetic studies in canines, in order to identify genetically-based poor or extensive drug metabolizers. This, together with more extensive in vitro drug screening for CYP2C41 substrates will help to determine the clinical relevance of CYP2C41, and to optimize drug treatment. Although the relative abundance of the CYP2C41 protein in the canine liver seems to not be very high, this CYP could substantially contribute to hepatic drug metabolism in dogs expressing CYP2C41 from both alleles and, when CYP2C41 shows higher catalytic activity to a given drug than other hepatic metabolic enzymes.